Hemodynamic Changes of the Cerebral Circulation after Stent-Protected Carotid Angioplasty - Niesen, Wolf-Dirk (AJNR Am J Neuroradiol, 2004)
BACKGOUND AND PURPOSE: Stent-protected carotid angioplasty (SPAC) is an option for treating cervical symptomatic high-grade internal carotid artery (ICA) stenosis. So far, knowledge about hemodynamic changes in the early postinterventional phase is limited. The purpose of this study was to evaluate these changes. METHODS: Thirty-four consecutive patients with a high-grade ICA stenosis (according to European Carotid Surgery Trial criteria) and 10 healthy volunteers were enrolled. Hemodynamics of the cerebral circulation were assessed before and within 6 hours after SPAC. ICA flow volume, cerebral blood volume flow (CBVF), and collateral flow volume were sonographically assessed. The ratio of flow velocities in the middle cerebral artery (MCA) ipsilateral to the ICA stenosis was calculated and compared with that in the contralateral MCA. This ratio was designated rMCA. RESULTS: Preinterventional CBVF, ICA flow volume, and rMCA were significantly reduced compared with results in healthy volunteers. After SPAC, CBVF, ICA flow volume, and rMCA increased significantly. The rMCA did not exceed 1.0. Collateral flow volume decreased in patients with posterior collateral flow only. Postinterventional CBVF and ICA flow volume in patients did not differ from values in healthy volunteers. CONCLUSION: Cerebral hemodynamics appear to be impaired in patients with symptomatic high-grade ICA stenosis. After SPAC, hemodynamic parameters normalize within 6 hours. We did not detect hyperperfusion. However, flow volume in the contralateral ICA remains increased in patients with former anterior cross-filling.